Leadership, organizational practices, and individual attributes as determinants of psychological empowerment and its effects in banking: a Scopus-based review - Quiñones Borda, Jorge Victor (2025)
This systematic review examines the causes and effects of psychological empowerment in the banking industry, an underexplored area in organizational behavior. Analyzing 47 Scopus-indexed studies published between 2004 and 2024, this study focuses on both the determinants and outcomes of psychological empowerment. Key findings highlight the role of transformational and ethical leadership, high performance work systems, and supportive organizational practices in empowering employees. Psychological empowerment enhances creativity, innovation, job performance, satisfaction, and retention. However, regional and methodological differences in the studies may limit the generalizability of the results. This review highlights the significance of empowerment strategies in fostering organizational success and offers actionable recommendations for managers to cultivate environments where employees feel motivated and valued. By addressing leadership approaches, organizational practices, and employee attributes, this study provides insights into enhancing engagement and performance in the banking sector. Future research should explore underrepresented regions to develop a more comprehensive understanding of psychological empowerment in banking.